2019
DOI: 10.1186/s40359-019-0285-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Japanese version of the three-item loneliness scale

Abstract: Background Loneliness is a major risk factor for mental and physical health worldwide. The Three-Item Loneliness Scale (TIL Scale; Hughes et al., 2004) has been widely applied to measure loneliness in a simplified format, but no validated Japanese version has been developed. This study adapted the TIL Scale into Japanese and tested its reliability and validity. Methods The original English version of the TIL Scale was translated into Japanese, and the expressions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 26 publications
8
52
1
2
Order By: Relevance
“…Surprisingly, we found no relationships between whether a person lives alone or with a partner and the subjective perceptions of passivity, isolation and loneliness. This finding is in contradiction to most other studies, which reported living alone among the key determinants of loneliness (Cornwell and Waite, 2009;Tomstad et al, 2017;Igarashi, 2019). No significant differences in the perceptions (of space-time constraints and socio-spatial isolation) between three studied cities have been detected, which indicates a relatively similar quality of life of older people in the regional cities in this study.…”
Section: Relationships Between Daily Activity Patterns and Socio-spatial Isolationcontrasting
confidence: 99%
“…Surprisingly, we found no relationships between whether a person lives alone or with a partner and the subjective perceptions of passivity, isolation and loneliness. This finding is in contradiction to most other studies, which reported living alone among the key determinants of loneliness (Cornwell and Waite, 2009;Tomstad et al, 2017;Igarashi, 2019). No significant differences in the perceptions (of space-time constraints and socio-spatial isolation) between three studied cities have been detected, which indicates a relatively similar quality of life of older people in the regional cities in this study.…”
Section: Relationships Between Daily Activity Patterns and Socio-spatial Isolationcontrasting
confidence: 99%
“…A three-item version of the loneliness scale has been developed by Hughes et al (Hughes, Waite, Hawkley, & Cacioppo, 2004), which has been referenced in notable related studies (Steptoe, Shankar, Demakakos, & Wardle, 2013) and is being translated and validated in other contexts (Igarashi, 2019). The three items were drawn from the dominant first factor to represent the loneliness construct.…”
Section: Discussionmentioning
confidence: 99%
“…The three-item version was used in a large sample survey; however, it did not provide data on psychometric properties, except the Cronbach's a (.72), and the correlation between the original R-ULS was .82 (p < .001). The three items were also tested in Japanese version among 1,520 online participants (Igarashi, 2019). The Japanese version provided a Cronbach's a of .81 and essential unidimensionality.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Recent research has indicated that the Japanese version of the Three-Item Loneliness Scale is similarly valid and reliable. 22 , 23 Two loneliness measures were analysed. Following the lead of previous studies, 24 , 25 a dummy variable was created where a score of ≥6 was categorised as lonely.…”
Section: Methodsmentioning
confidence: 99%